Implementation of E-HRM in the Ministry of Public Works and Public Housing - Farhana Farhana; Endah Labdhameirina; Mediaty Mediaty (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2022)
The Utilization of information technology systems is meant to be supported or encouraged organizations to achieve its organizational goals. This utilization is used not only in business sector, but also in the public sector. In achieving productivity and service efficiency, an integrated system is needed, so that the provision of services, the collection and processing of data can be done in a more efficient, transparent, orderly, fast, easy, integrated and secure manner. In making Policies in order to increase work efficiency and effectiveness in organizations needs to implement a Management Information System as a basis for decision making, management and policies, especially in terms of employee management. The Electronic Personnel Management System at the Ministry of Public Works and Public Housing manages personnel which covers all civil servant management activities, namely a personnel data management application called eHRM (Electronic Human Resource Management The aim of this research is to determine the role of employees in updating data and the benefits felt by users (employees) when using the e-HRM application at the PUPR Ministry. Qualitative method is used in this research. The results of the research shows that e-HRM is an effort to move manual processes to electronic ones so that personnel processes are fast, precise and up-to-date as well as making the administrative process of civil servants easier, one of which is promotion so that employees are required to always update their personal data so that the promotion process runs smoothly without constraints as well as providing a number of key benefits for organizations, such as increasing efficiency and reducing costs associated with Human Resource Management, facilitating the shift of HR's role to a more strategic level and improving client services, from manual administrative handling of entities to online-based systems.